The Eagle's Quill - Thomson, Sarah L. (New York : Bloomsbury, 2017)
In Glacier National Park, middle school geniuses Sam, Martina, and Theo follow clues related to Thomas Jefferson as they tackle a new round of puzzles, riddles, and traps to find the next key left behind by the Founding Fathers, but Gideon Arnold, descendant of the infamous Benedict Arnold, is hot on their trail.
Keywords: Jefferson, Thomas, -- 1743-1826 -- Fiction; Puzzles -- Fiction; Antiquities -- Fiction; Secret societies -- Fiction; Glacier National Park (Mont.) -- Fiction